2006
DOI: 10.1099/ijs.0.63921-0
|View full text |Cite
|
Sign up to set email alerts
|

Marinomonas polaris sp. nov., a psychrohalotolerant strain isolated from coastal sea water off the subantarctic Kerguelen islands

Abstract: Two aerobic, psychrohalotolerant, motile bacterial isolates, CK13 T and CK16, isolated from sea-water samples collected off the subantarctic Kerguelen island, were characterized by using a polyphasic taxonomic approach. On the basis of 16S rRNA gene sequence data, the strains were 99?6 % similar and exhibited 93-97 % similarity with the seven recognized species of Marinomonas. The most closely related species were Marinomonas pontica and Marinomonas primoryensis, with 97 and 96 % similarity at the 16S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…As well as Pseudoalteromonas species, Marinomonas members have been isolated from different Antarctic environments (Bowman et al , 1997b; Bozal et al , 2003; Prabagaran et al , 2005; Shivaji et al , 2005; Gupta et al , 2006). Because their antibacterial activity has, to our knowledge, not been reported previously, these bacteria could be a novel source of antimicrobial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…As well as Pseudoalteromonas species, Marinomonas members have been isolated from different Antarctic environments (Bowman et al , 1997b; Bozal et al , 2003; Prabagaran et al , 2005; Shivaji et al , 2005; Gupta et al , 2006). Because their antibacterial activity has, to our knowledge, not been reported previously, these bacteria could be a novel source of antimicrobial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The number of species in this genus has increased during recent years, after the initial description of the genus by Van Landschoot & De Ley (1983). At the time of writing, the list of species with validly published names in the genus Marinomonas included M. communis and M. vaga (formerly Alteromonas communis and A. vaga ; Van Landschoot & De Ley, 1983; Baumann et al , 1972), M. mediterranea (Solano & Sanchez-Amat, 1999), M. primoryensis (Romanenko et al , 2003), M. pontica (Ivanova et al , 2005), M. dokdonensis (Yoon et al , 2005), M. aquimarina (Macián et al , 2005), M. ushuaiensis (Prabagaran et al , 2005), M. polaris (Gupta et al , 2006), M. ostreistagni (Lau et al , 2006), M. arctica (Zhang et al , 2008), M. basaltis (Chang et al , 2008), M. arenicola (Romanenko et al , 2009), M. balearica and M. pollencensis (Espinosa et al , 2010). M. brasilensis has since been added to the genus and M. communis and M. basaltis have been recognized as heterotypic synonyms (Chimetto et al ., 2011).…”
mentioning
confidence: 99%
“…The results of the polar lipid analysis are presented in the species description. The major phospholipids, phosphatidylethanolamine and phosphatidylglycerol, also occur in many related marine isolates (Ivanova et al, 2000(Ivanova et al, , 2005Gupta et al, 2006). Analyses of quinones revealed that the novel strain has a major peak corresponding to Q8 (95 %) and two minor peaks of about the same size corresponding to unidentified components.…”
mentioning
confidence: 97%